ANALISIS KEMANDIRIAN ANAK USIA 5-6 TAHUN DI TK EDUCATION 21 KULIM KOTA PEKANBARU - Yanti Harahap, Eka Novi; Zulkifli N, Zulkifli N; Solfiah, Yeni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study aims to analyze the independence of children aged 5-6 years in Education Kindergareten 21 Kulim Pekanbaru City. The population is all children aged 5-6 years in Education Kindergarten 21 Kulim Pekanbaru City as many 57 children. The sample of the study is 36 children. The type of this research is descriptive with quantitative methods. Data collection techniques used are observation sheets. The sampling technique used in this study is simple random sampling. Data analysis techniques using percentage formulas, to find the number of scores of children's independence with 7 indicators namely controlling emotions, confidence, responsibility, discipline, cleverness, sharing and controlling emotions. The percentage of the independence of children aged 5-6 years in Education Kindergarten 21 Kulim Pekanbaru City amounting to 48.01% is in the criteria of MB (starting to develop)Keyword: independence of children aged 5-6 years